Gastrointestinal schwannomas: a rare but important differential diagnosis of mesenchymal tumors of gastrointestinal tract - Mekras, Alexandros; Krenn, Veit; Perrakis, Aristotelis; Croner, Roland S.; Kalles, Vasileios; Atamer, Cem; Grützmann, Robert; Vassos, Nikolaos (BMC Surgery, 2018)
BACKGROUND: Schwannomas of gastrointestinal tract are rare, mostly benign and notably different neoplasms from conventional schwannomas that arise in soft tissue or the central nervous system. These tumors are of clinical importance since they should always be considered in the differential diagnosis of submucosal lesions of gastrointestinal tract. METHODS: Seven patients with a pathologically proven gastrointestinal schwannoma were identified in our series of mesenchymal tumors and reviewed retrospectively. Clinicopathological and immunohistochemical parameters along with the follow-up results were analysed. RESULTS: The series included two males and five females, with a mean age 69 years (range, 39-81). Most patients were asymptomatic on presentation, except for two patients with abdominal pain. In the other cases (n = 5), the tumor was an incidental finding during other medical, imaging or surgical procedures. The tumors were located in the stomach (n = 4) and in the small intestine (n = 3) with an average size of 29 mm (range, 12-70). A preoperative diagnosis was achieved only in one case with a CT-guided core biopsy. Otherwise the clinical, intraoperative, endoscopic or radiological findings were unspecific. Patients with gastric tumor underwent either laparoscopic (n = 2) or open (n = 2) gastric wedge resection of the tumor; in the cases of intestinal tumor (n = 3) a segmentectomy was performed. Pathological examination revealed solid homogenous tumors, which were highly cellular and composed of spindle cells with positive staining for S100 protein, and confirmed the diagnosis of schwannoma. All tumors were negative for c-Kit, smooth muscle actin, desmin and DOG-1 and showed very low proliferation index. There were negative resection margins and no malignant variants were recognized. At an average follow-up of 60 months (range, 24-185) all patients were free of disease with no signs of recurrence or metastases and acceptable gastrointestinal function. CONCLUSIONS: Schwannomas are rare, slow-growing and mostly asymptomatic gastrointestinal mesenchymal tumors. They are difficult to be diagnosed preoperatively as endoscopic and radiological findings are nonspecific but histological and immunohistochemical features are of paramount importance to differentiate between benign and malignant schwannomas, or other spindle cell sarcomas. The treatment of choice is complete surgical excision without a conclusive preoperative diagnosis, and the long-term outcome is excellent as these lesions are mostly benign.
EVALuna2:210708